2020
DOI: 10.1002/ijc.33161
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of anlotinib in 45 patients with relapsed small cell lung cancer

Abstract: The purpose of this prospective phase II clinical trial was to investigate the efficacy and safety of anlotinib in patients with relapsed small cell lung cancer (SCLC). Fortyfive patients with relapsed SCLC were enrolled and treated with anlotinib (one cycle of 12 mg daily for 14 days, discontinued for 7 days, and repeated every 21 days) until disease progression or intolerance of treatment. The primary end point was progressionfree survival (PFS). Secondary end points were overall survival (OS), disease contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Anlotinib has yielded favorable outcomes in lung cancer and was approved for third-line or further-line therapy for both NSCLC [ 117 ] and SCLC [ 118 ] by NMPA. In its phase II trial for patients with relapsed SCLC, a mPFS of 4.1 months was reported [ 119 ]. Similarly, apatinib presented a mPFS of 5.4 months in patients with extensive-stage SCLC after failure of two or more lines of chemotherapy [ 120 ].…”
Section: Vegfr-associated Multi-targeted Tkismentioning
confidence: 99%
“…Anlotinib has yielded favorable outcomes in lung cancer and was approved for third-line or further-line therapy for both NSCLC [ 117 ] and SCLC [ 118 ] by NMPA. In its phase II trial for patients with relapsed SCLC, a mPFS of 4.1 months was reported [ 119 ]. Similarly, apatinib presented a mPFS of 5.4 months in patients with extensive-stage SCLC after failure of two or more lines of chemotherapy [ 120 ].…”
Section: Vegfr-associated Multi-targeted Tkismentioning
confidence: 99%
“…Moreover, they indicated that limited-stage patients had a longer OS than that of extensive-stage patients. 19 However, Chen et al reported only 2.6 months of PFS in SCLC patients treated with anlotinib in the real-world without reporting data of OS and AEs. 20 Zhang et al reported an advanced SCLC patient treated with anlotinib experienced 11 months duration of response after four lines of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Overall survival (OS) was defined as the duration from the onset of apatinib treatment to death of the patient from any cause. 26 For those who were still receiving apatinib treatment or alive, survival end points were censored at the date of cut-off. The final cut-off date was November 30, 2020.…”
Section: Methodsmentioning
confidence: 99%